(untitled) (ARQUISUR Revista, 2024)
This article presents partial results of research conducted in the framework of a Master’s degree in Construction of Architectural Works at the Faculty of Architecture, Design and Urbanism, Universidad de la República (Uruguay). This research is being funded for the period between 2024 and 2025 by the Sectoral Commission for Scientific Research (CSIC, by its initials in Spanish) within the project called Géneras, in the framework of the call for initiation research projects. The methodology being used involved collective interviews with members of housing cooperatives and answers in a validated questionnaire within the Thesis work. The objective is to visualize the relationship between housing ownership in Union Housing Plans (PVS, by its initials in Spanish) and the gender of homeowners in order to identify (or not) gender inequities. After surveying four cooperatives, it was found that most homeowners are female, but there are also some cases of shared ownership. In this case, the changes made by Law Nr. 19,580 have not produced greater effects since female homeowners are the initial female heads of the household when they registered as a family unit and there have been no changes in ownership along the construction and occupancy of the houses.